PENGARUH TATA KELOLA PERUSAHAAN DAN PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAAN TERHADAP KINERJA KEUANGAN DENGAN MANAJEMEN LABA SEBAGAI VARIABEL MEDIASI - Rosa Priskila Sitanggang; Dwi Ratmono (Diponegoro Journal of Accounting, 2019)
This research aimed to analyze the good corporate governance and corporate social responsibility disclosure on financial performance as well as through earnings management as a mediating variable. The dependent variable in this research is financial performance measured by proxies ROA, EPS and TOBIN’S Q, while the independent variables in this research are the good corporate governance measured by proxies the independent board of commissioners proportion, audit comitte, sum of meeting audit comitte and corporate social responsibility measured use index 91 Global Reporting Initiative. Also, this research adds earnings management as mediating variable.This research used 98 samples of manufactur companies listed on The Indonesia Stock Exchange in 2016 & 2017. The data used in this study were analyzed using partial least square and carried out with the help of software WarpPLS 6.0 to examined the hypothesis.The result shows that there is positive effect good corporate governance on financial performance, no effect corporate social responsibility disclosure on financial performance, no effect good corporate governance on earnings management, there is positive effect corporate social responsibility disclosure on earnings management, there is positive effect earnings management on financial performance,no effect mediation earning management on the good corporate governance to financial performance and there is positive effect mediation earnings management on corporate social performance to financial performance.